Study of Association Between Glycated Hemoglobin and Lipid Profile in Type 2 Diabetes Mellitus in Tertiary Care Center - Pandey, Tilchan; Khanal, Jivan; Godar, Krishan Chandra (Journal of Lumbini Medical College, 2020)
Introduction: Diabetes is one of the major burdens of non-communicable disease causing morbidity and mortality. Glycated hemoglobin (HbA1c) has been used as a tool to monitor glycemic control in patients with type 2 diabetes mellitus and elevated HbA1c value is considered an independent risk factor for dyslipidemia. Methods: A total of 120 patients with type 2 diabetes mellitus were enrolled in this cross-sectional study. Means with standard deviation were used for age, height, weight and fasting blood sugar and Pearson correlation test was applied to identify correlation between Glycated hemoglobin (HbA1c) and lipid profile. Comparison of means was done by Student 't' test in parametric data within the two groups. P value less than 0.05 was considered significant. Results: The mean HbA1c of male and female patients were 8.35±1.77 and 8.65±1.95 respectively. Among patients with good glycemic control, mean total cholesterol and mean high density lipoprotein were higher than poor glycemic control patients. Patients with poor glycemic control had higher mean triglyceride and low density lipoprotein than good glycemic control patients. Correlation coefficient for various components of lipid profile and HbA1c were: total cholesterol (r=0.189, p=0.038, n=120), triglyceride (r=0.418, p<0.01, n=120), low density lipoprotein (r=0.673,p<0.01,n=120) and high density lipoprotein ( r=-0.683,p<0.01, n=120). Conclusion: There was a significant moderate correlation between HbA1c and lipid profile. Lipid profile values were significantly higher in poor glycemic control than good glycemic control patients. Hence, HbA1c can be considered as a surrogate marker for dyslipidemia in type 2 DM patients.